Oxidized Forms of Olive Oil Secoiridoids: Semisynthesis, Identification and Correlation with Quality Parameters - Antoniadi, Lemonia; Angelis, Apostolis; Stathopoulos, Panagiotis; Bata, Eirini-Maria; Papoutsaki, Zoe; Halabalaki, Maria; Skaltsounis, Leandros A. (Planta Medica, 2022)
Secoiridoids is the prominent chemical class of olive oil polar constituents and are characterized by significant biological properties. They are abundant in different chemical forms and relatively high concentrations compared to other components, while prone to oxidation due to their chemical motif. In recent years, oxidized derivatives of secoiridoids have been reported, either as natural constituents of olive oil or as components which are gradually formed in all stages of its production and storage. The mono-oxidized forms of oleocanthal and oleacein named as the respective acids have been recently isolated from olive oil and unambiguously structurally characterized. Other oxidized forms of elenolic acid or more complex secoiridoids, such as those of oleuropein and ligstroside aglycones are also sporadically mentioned in the literature. No further information is provided since they have not been isolated in pure form in order to be accurately identified. Most of the time, they are generally referred as oxidized forms of the parent compounds and commonly identified based on mass spectrometric data. In the current study, the semi-synthesis of the main oxidized olive oil secoiridoids, i.e., oleocanthalic acid, oleaceinic acid, EDA acid, carboxylic form of elenolic acid, carboxylic form of ligstroside aglycon, and carboxylic form of oleuropein aglycon is described starting from the corresponding aldehydic derivatives, using SeO2/H2O2 as oxidative agents. Furthermore, their presence in a number of Greek olive oils was investigated as well, as possible correlation thereof with quality parameters.
Keywords: Oxidized Secoiridoid Compounds; Oleocanthal; Oleocanthalic acid; Semi-synthesis; Olive oil; Quality parameters; Olea europaea; Oleaceae